2022
DOI: 10.3390/ijms232113296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PnTCP2 in the Lobed Leaf Formation of Phoebe neurantha var. lobophylla

Abstract: A lobed leaf is a common trait in plants, but it is very rare in Lauraceae plants, including species of Phoebe. In the study of germplasm resources of Phoebe neurantha, we found lobed leaf variant seedlings, and the variation could be inherited stably. Studying the lobed leaf mechanism of P. neurantha var. lobophylla can offer insight into the leaf development mechanism of woody plants. RNA-seq and small RNA-seq analysis results showed that a total of 8091 differentially expressed genes (DEGs) and 16 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…miRNAs are fundamental regulators of plant growth and development. A subset of CIN -like genes in many plants analyzed to date are targets of the miR319 and miR319-TCPs regulatory systems, which are widely involved in the development of plant roots ( Baulies et al., 2022 ), leaves ( Koyama et al., 2017 ; Sun et al., 2022 ), flowers ( Nag et al., 2009 ; Silva et al., 2019 ), and plant immunity ( Lopez et al., 2015 ). Interestingly, we found that miR159 shares the same target genes as miR319.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are fundamental regulators of plant growth and development. A subset of CIN -like genes in many plants analyzed to date are targets of the miR319 and miR319-TCPs regulatory systems, which are widely involved in the development of plant roots ( Baulies et al., 2022 ), leaves ( Koyama et al., 2017 ; Sun et al., 2022 ), flowers ( Nag et al., 2009 ; Silva et al., 2019 ), and plant immunity ( Lopez et al., 2015 ). Interestingly, we found that miR159 shares the same target genes as miR319.…”
Section: Discussionmentioning
confidence: 99%